Penerapan Ultrasonic Assisted Extraction sebagai Teknologi Modern dalam Pelatihan Isolasi Minyak Atsiri Berbahan Dasar Kopi kepada Siswa Siswi SMK Yasmu Gresik - Mustikaningrum, Mega; Fiska Yohana Purwaningtyas; Aidayatul Sholichatin Maqfiroh; Rosida Maya Fardiana; Kinantih Puspa Kumala; Nafiatur Rahmah; Muhammad Bagas Supari (Jurnal Pengabdian Masyarakat dan Lingkungan, 2026)
The development of science related to natural resource extraction is quite rapid, especially in Indonesia. This is due to the increasing understanding of the use of natural resources that can be applied in various fields. One renewable, environmentally friendly method is Ultrasonic-Assisted Extraction (UAE), which uses cavitation energy as a source of energy in the extraction process. The training was carried out through the stages of delivering theoretical material on the characteristics of essential oils, the basic principles of ultrasonic cavitation, and UAE process parameters. This stage was followed by a demonstration of the use of ultrasonic extraction equipment and hands-on practice. The results of the activity showed that students were able to master the operational steps of UAE, understand the factors that influence extraction efficiency, and conduct initial evaluations of the quality of the resulting oil. Furthermore, this training also increased students' technological literacy regarding the importance of implementing environmentally friendly extraction methods oriented towards process efficiency.